Charismatic Prophecy in the Pentecostal Assemblies of Canada - Barkley, Stephen D. (My University, 2022)
Prophecy is a major theme in Scripture and in contemporary practice in Pentecostal and charismatic settings. At its simplest, prophecy can be understood as a message from God delivered through a spokesperson to an audience, usually in the form of a revelatory experience. Despite the significance of prophecy in the history of Pentecostalism, the experiential coherence between modern-day charismatic prophets and Old Testament prophets has not been directly examined. Consideration of the literature shows conflicting messages. The application of biblical and historical studies tends to emphasize the divide between the Old Testament prophets and modern-day charismatic prophets while practical theological studies emphasize coherence. The heart of this practical theological study is a phenomenological investigation of the practice of charismatic prophecy in the Canadian context. Five textural and three structural elements are identified: Prophets recognize the presence of God, receive the prophetic impulse, discern the source and recipient of the message, release the prophetic message or act, and experience attendant physical and emotional sensations. The way that prophets experience this phenomenon is impacted by their mentoring, setting, and response to failure. This phenomenological description was then compared with the experience of Jeremiah to evaluate the level of coherence. Aside from uncertainty regarding the distinction of the first two textural components and the issue of discernment, a strong level of coherence was discovered between the Old Testament prophets and modern-day charismatic prophets. Jeremiah and modern-day Canadian prophets experience the phenomenon of prophecy in very similar ways. This high level of coherence leads to three conclusions. First, the application of biblical and historical studies that emphasize the discontinuity between the Old Testament prophets and modern-day charismatic prophets should be resisted in light of the data. This application—often based on a concern to safeguard the unique authority of Scripture from contemporary prophetic messages—is unnecessary since Canadian prophets hold a high value of Scripture that can be seen in the experience of Jeremiah himself. Second, Pentecostals should expand their narrative understanding backward in time to include the Old Testament prophetic lineage. Third, modern-day charismatic prophets should be encouraged to return to the Old Testament prophets for a deeper understanding of their practice.
An Old Testament Perspective
Keywords: Prophecy; Old Testament prophets